How do People with Disabilities Evaluate the Quality of Social Services? - Čiapaitė, Laurita; Vaitkevičienė, Asta (Socialinė teorija, empirija, politika ir praktika, 2020)
In this article we analyse the quality of social services from the perspective of people with disabilities and we analyse other social services quality studies that use the EQUASS system or the SERVQUAL model. We show the contrast between the high quality ratings reported by social workers and unmet expectations of the services’ recipients. It is argued that the difference may be due to methodological errors in choosing one or another research method, and the phenomenon of social workers’ conformism, which can be supported also by the peculiarities of Lithuania’s long-term social policy. It is proposed that the SERWQUAL model be used for the study of the quality of social services, which is flexible with regards to the needs of service users. Triangulation of research methods was used to analyse the data. We show evaluation of the quality of social services according to the 5 dimensions of the SERWQUAL model: tangibles, reliability, responsiveness, assurance (certainty) and sensitivity (empathy).